Secular Trends in Diabetes-Related Preventable Hospitalizations in the United States, 1998–2006 - Wang, Jing (American Diabetes Association, 2009)
OBJECTIVE: To examine secular trends in diabetes-related preventable hospitalizations among adults with diabetes in the U.S. from 1998 to 2006. RESEARCH DESIGN AND METHODS: We used nationally representative data from the National Inpatient Sample to identify diabetes-related preventable hospitalizations. Based on the Agency for Healthcare Research and Quality's Prevention Quality Indicators, we considered that hospitalizations associated with the following four conditions were preventable: uncontrolled diabetes, short-term complications, long-term complications, and lower-extremity amputations. Estimates of the number of adults with diabetes were obtained from the National Health Interview Survey. Rates of hospitalizations among adults with diabetes were derived and tested for trends. RESULTS: Age-adjusted rates for overall diabetes-related preventable hospitalizations per 100 adults with diabetes declined 27%, from 5.2 to 3.8 during 1998–2006 (P(trend) < 0.01). This rate decreased significantly for all but not for short-term complication (58% for uncontrolled diabetes, 37% for lower-extremity amputations, 23% for long-term complications [all P < 0.01], and 15% for the short-term complication [P = 0.18]). Stratified by age-group and condition, the decline was significant for all age-condition groups (all P < 0.05) except short-term complications (P = 0.33) and long-term complications (P = 0.08) for the age-group 18–44 years. The decrease was significant for all sex-condition combination subgroups (all P < 0.01). CONCLUSIONS: We found a decrease in diabetes-related preventable hospitalizations in the U.S. from 1998 to 2006. This trend could reflect improvements in quality of primary care for individuals with diabetes.